2004
DOI: 10.1208/pt050455
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration of ibuprofen with talc by novel crystallo-co-agglomeration technique

Abstract: The purpose of this research work was to obtain directly compressible agglomerates of ibuprofen with talc by a novel crystallo-co-agglomeration (CCA) technique, which is an extension of spherical crystallization. Ibuprofen-talc agglomerates were prepared using dichloromethane (DCM)-water as the crystallization system. DCM acted as a good solvent for ibuprofen as well as a bridging liquid for agglomeration of crystallized drug with talc. The agglomerates were characterized by differential scanning calorimetry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Mainly, recrystallization of the drug during agglomeration generates the miniscular dosage form. The miniscular dosage form of Linezolidtalc in this new study showed sustained drug release fitting the Higuchi matrix model, whereas sustained zero-order drug release was reported for ibuprofen-talc [29]. …”
Section: Fig 5: X-ray Powder Diffraction Pattern Of Pure Linezolid Amentioning
confidence: 62%
“…Mainly, recrystallization of the drug during agglomeration generates the miniscular dosage form. The miniscular dosage form of Linezolidtalc in this new study showed sustained drug release fitting the Higuchi matrix model, whereas sustained zero-order drug release was reported for ibuprofen-talc [29]. …”
Section: Fig 5: X-ray Powder Diffraction Pattern Of Pure Linezolid Amentioning
confidence: 62%
“…There was a research paper on the agglomerates formed by ibuprofen and talc [32] . The percentageprocess yield is of 95-96% w/w.…”
Section: Significance Of Crystallo Co Agglomerationmentioning
confidence: 99%
“…Blank talc agglomerates were used as an inert core or coating substrate by the aid of which drug loaded talc pellets can be prepared. This drug loaded talc pellets have better mechanical, micromeritical and compressional properties [7][8][9] . With the selection and use of appropriate polymers, it is possible to compress into tablet intermediate and or spensules, which possess all advantages, required in the design of MUPS.…”
Section: Introductionmentioning
confidence: 99%
“…It is a modification of the spherical crystallization techniques described above, in which a drug is crystallized and agglomerated with an excipient (48,49) or with another drug (50). Similar to spherical agglomeration, a good solvent is used in this method to solubilize the drug, a poor solvent to cause drug crystallization and the bridging liquid, which is immiscible with the poor solvent, to form liquid bridges during the agglomeration process.…”
Section: Crystallo-co-agglomerationmentioning
confidence: 99%